Penentuan Jalur Terpendek Pendistribusian Barang Jalur Nugraha Ekakurir (JNE) Menggunakan Algoritma Semut (Studi Kasus JNE Dewi Sartika Palu) - Musdalipa; Sahari, A; Najar, A M (Program Studi Matematika, Universitas Tadulako, 2021)
Nowasday, it is often done traveling from one place or location to another by considering the path or the shortest route to be traveled. In determining the shortest route by implementing the ant algorithm to determine the shottest route. This case is a case of the traveling salesmen problem (TPS) namely visiting all location points starting from the starting point and ending at the starting point again. Case study in this research is delivery data of JNE courier palu. The sample used is 13 points which are then resolved using the ant algorithm adopts the ant work method to get the shortest route. The use of the ant algorithm in this case is limited to one cycle or one iteration (NC=1) so that the best route for the first cycle is obtained JNE Gudang utama dewi sartika palu( JNE jalan banteng No.8a biromaru palu selatan ( JNE basuki rahmat ( ), JNE jalan anoa No.107 pau selatan ( JNE diponegoro lere palu barat( JNE emysaelan No.20 palu selatan ( JNE sisingamangaraja palu ( JNE jalan kimaja palu barat ( ), JNE krajalemba No.7 sigi biromaru ( JNE jalan tombolotutu palu JNE samratulangi No.66 A palu ( ), JNE tondo kamus mantikulore ( JNE diponegoro lere palu barat ( anddcome back to JNE gudang utama dewi sartika palu ( ) with a distance of 56.4 km.